Alas, Babylon a novel - Frank, Pat 1908- (Philadelphia Lippincott, 1959)
A story of a group of people who rely on their own courage and ingenuity to survive in a town which escaped nuclear bombing.
Keywords: Survival -- Fiction; Nuclear warfare -- Fiction